(untitled) (Global Journal of Human-Social Science, 2012)
Persons with disabilities also face multiple physical political social economic and handicaps hampering their freedom of participation and development in society These barriers include misunderstanding and stigmatization of the abilities and aspirations of persons with disabilities There is also a pronounced lack of informational data rules and regulations rehabilitation centers and mainstreaming and specialized services for persons with disabilities The any objective of the present study to find out the problems faced by the parents of disables people The present study was conducted in District Faisalabad Multistage sampling technique was used for data collection At the first stage two institutions Govt Special Education Center Jaranwala and Govt Special Education Center Tandianwala were selected purposively At the second stage made a list of rural disabled children s mothers from the school record At the third stage 120 mothers 60 from each institute were selected randomly from the list